The Wet Method of Enriching Quartz Sand for the Production of Glass (Eurasian Research Bulletin, 2022)
Method of moisture enrichment of quartz sands is required in the glass industry. In recent years, a number of information about the wet process and used industrial equipment for the enrichment of quartz sands have been published. This article discussed the wet method of enriching quartz sands for glass production.